Experts’ judgment and perception of android-based materials for sports massage learning - Boby Ardianzah Efendy; Muhsana El Cintami Lanos; Edi Setiawan; Ruslan Abdul Gani (Journal Sport Area, 2023)
This study aims to obtain the results of the product validation of the Android-based massage learning material model that has been designed through expert judgment and perception. The experts involved in the research are massage, learning, and media experts. The research method uses quantitative research in order to analyze quantitative data using IBM SPSS 25.0. Descriptive statistical results percentage. The results of the study concluded that the android-based massage learning material was feasible to use. Some inputs for product improvement are the addition of instructions for using the application, a display with a spread pattern, adding instructional content, simplifying the display, a simulation video, adding competence according to the Indonesian National Framework of Qualifications format, and lowering the file capacity to make it easier to access by the Android OS. The results of this study have implications for the understanding of lecturer who have developed appropriate and effective learning material.